2013
DOI: 10.1254/jphs.13019fp
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Luteolin on an Oxidative-Stress Model Induced by Microinjection of Sodium Nitroprusside in Mice

Abstract: Abstract. Accumulating lines of evidence showed that luteolin, a polyphenolic compound, has potent neuroprotective effects. The purpose of this study was to examine whether luteolin can protect against sodium nitroprusside (SNP)-induced oxidative damage in mouse brain. Intrastriatal co-injection of luteolin (3 -30 nmol) with SNP (10 nmol) dose-dependently protected against brain damage and motor dysfunction. Oral administrations of luteolin (600 -1200 mg/kg) dosedependently protected against brain damage and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…We previously reported that Fe 2+ released from SNP induced oxidative stress and that oxidative stress plays a crucial role in brain damage. 10) We also reported that polyphenols such as luteolin and curcumin had inhibitory effects against the in vivo brain oxidative stress model. 11,12) However, it has not been examined whether compounds that activate the Nrf2-ARE pathway have preventive effects in the model.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…We previously reported that Fe 2+ released from SNP induced oxidative stress and that oxidative stress plays a crucial role in brain damage. 10) We also reported that polyphenols such as luteolin and curcumin had inhibitory effects against the in vivo brain oxidative stress model. 11,12) However, it has not been examined whether compounds that activate the Nrf2-ARE pathway have preventive effects in the model.…”
mentioning
confidence: 86%
“…10) We utilize this animal model as an in vivo brain oxidative stress model in mice. We previously reported that Fe 2+ released from SNP induced oxidative stress and that oxidative stress plays a crucial role in brain damage.…”
mentioning
confidence: 99%
“…Luteolin is a bioflavonoid present in many medicinal plants as well as in some commonly consumed fruits and vegetables including green leafy spices such as parsley, sweet peppers and celery [1113]. Previous studies showed that luteolin possess numerous beneficial medicinal properties such as antioxidant, antiinflammatory, and anti-allergic actions [1519]. Data from vitro studies also suggest a protective role of luteolin in the vascular vasculature and the beneficial effect of luteolin on inflammatory process and inflammatory associated CVD [1519].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that luteolin possess numerous beneficial medicinal properties such as antioxidant, antiinflammatory, and anti-allergic actions [1519]. Data from vitro studies also suggest a protective role of luteolin in the vascular vasculature and the beneficial effect of luteolin on inflammatory process and inflammatory associated CVD [1519]. In this context, luteolin at higher doses (≥ 25 μM) inhibited oxidized LDL and TNF-α-induced VCAM-1 expression [1519].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation